1987
DOI: 10.1021/jf00076a016
|View full text |Cite
|
Sign up to set email alerts
|

Residues of dimethoate and omethoate in peaches and apples following repeated applications of dimethoate

Abstract: Repeated applications of dimethoate were carried out on peaches and apple trees in order to establish the maximum number of dimethoate sprays that will give rise to residues complying with international maximum residue limits. Samples were analyzed by gas chromatography for the determination of dimethoate and its oxygen analogue, omethoate, over a period of 3-4 weeks after last spray. Only in the case of apples with seven applications, mean residues of dimethoate exceeded 1 ppm at the end of the preharvest int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Propetamphos and diazinon in sheep's wool were determined by &C/MS without cleanup of petroleum ether extracts (120). Dimethoate and omethoate were determined in peaches and apples by GC-FID after extraction and solvent partition cleanup (121). GC-FPD was used to determine mecarbam and its metabolites mecarboxon, diethoate, and diethoxon in cottonseeds (122).…”
Section: Organophosphorus (Op) Pesticidesmentioning
confidence: 99%
“…Propetamphos and diazinon in sheep's wool were determined by &C/MS without cleanup of petroleum ether extracts (120). Dimethoate and omethoate were determined in peaches and apples by GC-FID after extraction and solvent partition cleanup (121). GC-FPD was used to determine mecarbam and its metabolites mecarboxon, diethoate, and diethoxon in cottonseeds (122).…”
Section: Organophosphorus (Op) Pesticidesmentioning
confidence: 99%
“…A large number of papers have been published on the determination of omethoate by mass spectrometry-gas chromatography and voltammetry. [26][27][28][29][30][31][32][33][34][35] Djenaine De Souza et al reported on using an electroanalytical method for the determination of DCV using gold-disk microelectrodes. 36 Yanhong Bai et al reported the reduction of DCV and OMT residues by an O 2 plasma treatment.…”
Section: Introductionmentioning
confidence: 99%